2019
DOI: 10.1038/s41467-018-08230-6
|View full text |Cite
|
Sign up to set email alerts
|

WDR76 is a RAS binding protein that functions as a tumor suppressor via RAS degradation

Abstract: Stability regulation of RAS that can affect its activity, in addition to the oncogenic mutations, occurs in human cancer. However, the mechanisms for stability regulation of RAS involved in their activity and its roles in tumorigenesis are poorly explored. Here, we identify WD40-repeat protein 76 (WDR76) as one of the HRAS binding proteins using proteomic analyses of hepatocellular carcinomas (HCC) tissue. WDR76 plays a role as an E3 linker protein and mediates the polyubiquitination-dependent degradation of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 50 publications
4
44
0
Order By: Relevance
“…In addition, the prognostic summary in the Pathology Atlas for WDR76 in The Human Protein Atlas (Uhlen et al, 2017) lists WDR76 as an unfavorable prognostic marker in renal cancer, lung cancer, pancreatic cancer, and liver cancer. These links to cancer are supported by recent evidence of the role of WDR76 in regulating the RAS oncogene (Jeong et al, 2019).…”
Section: Wdr76 Conservation and Links To Human Diseasementioning
confidence: 71%
See 1 more Smart Citation
“…In addition, the prognostic summary in the Pathology Atlas for WDR76 in The Human Protein Atlas (Uhlen et al, 2017) lists WDR76 as an unfavorable prognostic marker in renal cancer, lung cancer, pancreatic cancer, and liver cancer. These links to cancer are supported by recent evidence of the role of WDR76 in regulating the RAS oncogene (Jeong et al, 2019).…”
Section: Wdr76 Conservation and Links To Human Diseasementioning
confidence: 71%
“…WDR76 has been linked to the CUL4-DDB1 ubiquitin ligase complex in mammals where WDR76 is involved in regulating circadian rhythms (Tamayo et al, 2015). In addition, recently Jeong et al have shown that the CUL4-DDB1-WDR76 ubiquitin ligase complex is vital for the regulation of RAS levels via a polyubiquitination-dependent degradation mechanism required for inhibition of proliferation, transformation, and invasion in liver cancer cells (Jeong et al, 2019). Collectively, these studies support the idea that WDR76 may be an ubiquitin ligase E3 linker protein.…”
Section: Introductionmentioning
confidence: 99%
“…For viral production, HEK293T cells were transfected with pLVX-GFP-Control, pLVX-GFP-WDR76, pLVX-GFP-WDR76ΔNLS, pLKO.1-shControl-GFP, or pLKO.1-shWDR76-GFP, [19] together with the viral packaging psPAX2 and viral envelope pMD2G plasmids at a 2:2:1 ratio. Then, D-WT and D-MT cells were transduced with each lentivirus.…”
Section: Methodsmentioning
confidence: 99%
“…WDR76 (WD Repeat protein 76) is an E3 ligase that suppresses tumorigenesis of human hepatocellular carcinoma (HCC) cells by destabilizing RAS [19]. WDR76 has been identified as one of the proteins that interacts with H-RAS in human HCC tissues and destabilizes all three major RAS isoforms, H-RAS, K-RAS and N-RAS [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation